Exploring the Pivotal Immunomodulatory and Anti-Inflammatory Potentials of Glycyrrhizic and Glycyrrhetinic Acids - Seidu A. Richard (Mediators of Inflammation)
Licorice extract is a Chinese herbal medication most often used as a demulcent or elixir. The extract usually consists of many components but the key ingredients are glycyrrhizic (GL) and glycyrrhetinic acid (GA). GL and GA function as potent antioxidants, anti-inflammatory, antiviral, antitumor agents, and immuneregulators. GL and GA have potent activities against hepatitis A, B, and C viruses, human immunodeficiency virus type 1, vesicular stomatitis virus, herpes simplex virus, influenza A, severe acute respiratory syndrome-related coronavirus, respiratory syncytial virus, vaccinia virus, and arboviruses. Also, GA was observed to be of therapeutic valve in human enterovirus 71, which was recognized as the utmost regular virus responsible for hand, foot, and mouth disease. The anti-inflammatory mechanism of GL and GA is realized via cytokines like interferon-γ, tumor necrotizing factor-α, interleukin- (IL-) 1β, IL-4, IL-5, IL-6, IL-8, IL-10, IL-12, and IL-17. They also modulate anti-inflammatory mechanisms like intercellular cell adhesion molecule 1 and P-selectin, enzymes like inducible nitric oxide synthase (iNOS), and transcription factors such as nuclear factor-kappa B, signal transducer and activator of transcription- (STAT-) 3, and STAT-6. Furthermore, DCs treated with GL were capable of influencing T-cell differentiation toward Th1 subset. Moreover, GA is capable of blocking prostaglandin-E2 synthesis via blockade of cyclooxygenase- (COX-) 2 resulting in concurrent augmentation nitric oxide production through the enhancement of iNOS2 mRNA secretion in Leishmania-infected macrophages. GA is capable of inhibiting toll-like receptors as well as high-mobility group box 1.